OARSI–OMERACT definition of relevant radiological progression in hip/knee osteoarthritis - Ornetti, P. (Osteoarthritis Cartilage, 2009)
BACKGROUND: Joint space width (JSW) evaluated in millimeters on plain X-rays is the currently optimal recognized technique to evaluate osteoarthritis (OA) structural progression. Data obtained can be presented at the group level (e.g., mean ± standard deviation of the changes). Such presentation makes difficult the interpretation of the clinical relevance of the reported results. Therefore, a presentation at the individual level (e.g., % progressors) seems more attractive but requires to determining a cut-off. Several methodologies have been proposed to define cut-offs in JSW: arbitrary chosen cut-off, cut-off based on the validity to predict a relevant end-point such as the requirement of total articular replacement or cut-off based on the measurement error such as smallest detectable difference (SDD). OBJECTIVES: The objective of this OARSI–OMERACT initiative was to define a cut-off evaluated in millimeters on plain X-rays above which a change in JSW could be considered as relevant in patients with hip and knee OA. METHODS: The first step consisted in a systematic literature research performed using Medline database up to July 2007 to obtain all manuscripts published between 1990 and 2007 reporting a cut-off value in JSW evaluated in millimeters at either the knee or hip level. The second step consisted in a consensus based on the best knowledge of the 11 experts with the support of the available evidence. RESULTS: Among the 506 articles selected by the search, 47 articles reported cut-off of JSW in millimeters. There was a broad heterogeneity in cut-off values, whatever the methodologies or the OA localization considered (e.g., from 0.12 to 0.84 mm and from 0.22 to 0.78 mm for Knee (seven studies) and hip (seven studies), respectively when considering the data obtained based on the reliability). Based on the data extracted in the literature, the expert committee proposed a definition of relevant change in JSW based on plain X-rays, on an absolute change of JSW in millimeters and on the measurement error e.g., calculation of the SDD using the Bland and Altman technique. The results of the analysis of JSW should be expressed in terms of a dichotomous variable (e.g., progressors yes/no): a patient with a change in JSW during the study over such SDD will fulfill the definition of “progressor”. Moreover, the pilot study aimed at evaluating the measurement error should be designed to reflect the different characteristics of the primary study in which the analysis of the radiological findings will be based on (patient’s characteristics, centers characteristics, readers). CONCLUSION: This initiative based on both an Evidence Based Medicine (Systematic Literature Research) and Expert Opinion approach resulted in a proposal of definition of relevant radiological progression in OA to be used as end-point in clinical trials and also recommendations on the conduct of the reliability study allowing such definition.